Author correction: Genome-wide association study of classical Hodgkin lymphoma identifies key regulators of disease susceptibility - Sud, Amit; Försti, Asta; Hemminki, Kari; Canzian, Federico; Brenner, Hermann (Nature Communications, 2019)
The original version of this Article contained an error in the spelling of a member of the PRACTICAL Consortium, Manuela Gago-Dominguez, which was incorrectly given as Manuela Gago Dominguez. This has now been corrected in both the PDF and HTML versions of the Article.
#Amit Sud, Asta Försti, Federico Canzian, The PRACTICAL consortium Kari Hemminki [und weitere]; The PRACTICAL consortium Hermann Brenner [und weitere]
Gesehen am 21.06.2019